Atopic dermatitis and ABO blood group - Gangopadhyay Dwijendra; Naskar Biswanath; Roy Alok Kumar (Wolters Kluwer Medknow Publications, 2006)
BACKGROUND: Atopic dermatitis is a chronic recurrent genetically determined skin disease affecting all age groups. PURPOSES: To study epidemiological and environmental factors, clinical patterns and the relationship of atopic dermatitis with ABO blood group system. METHODS: In 30 atopic dermatitis patients blood group distribution was compared with the distribution in 1500 relative donors of the blood bank of the same institute. FINDINGS: There were 18 males (60%) and 12 females (40%). Family and personal history of atopy were observed in 21 (70%(and 19 cases (63.3%) respectively. CONCLUSIONS: Blood group O subjects were significantly less in the study population in comparison to control. LIMITATION: Hospital based study with small sample size; hence the result cannot be generalized.